A combination of plant-based compounds and extracts acts nematicidal and induces resistance against Meloidogyne incognita in tomato - Degroote, Eva; Schoorens, Chloë; Pockelé, Stefaan; Stojilković, Boris; Demeestere, Kristof; Mangelinckx, Sven; Kyndt, Tina (Frontiers in Plant Science, 2024)
Considering the stricter European regulations for chemical pesticides (e.g. abolishment of the use of chemical soil fumigation products, such as methyl bromide), the need for more sustainable plant protection products is strongly increasing. In this research, Product X, an innovative mixture of bio-nematicidal compounds was developed and evaluated for efficacy. Product X showed a direct nematicidal effect against the root-knot nematode Meloidogyne incognita. In pot trials with tomato plants infected with M. incognita, Product X treatment lead to a significant reduction in nematodeinduced gall formation. mRNA-sequencing indicated alterations in phytohormone levels and ROSmetabolism in tomato roots upon treatment with Product X, which was subsequently biochemically validated. Increased levels of abscisic acid and peroxidase activity seem to be the main factors in the response of tomato plants to Product X. Long-term administration of Product X did not yield negative effects on tomato growth or yield. In conclusion, Product X provides a new interesting mix of bio-active compounds in the combat against root-knot nematodes.